Identification of mathematical models at heating special steel grades in furnaces - G. A. Anisovich; V. I. Timoshpolski; I. A. Trusova; S. M. Kabishov; R. B. Vice; Yu. V. Dyachenko (Литьë и металлургия, 2000)
The article gives the results of parametric identification of mathematical models of nonsymmetric heat- of metal in continuous pusher furnaces with powered hearth.